Communication Strategies Used by Students in the Exchange Program: Bridging Indonesian and Thailand - Sakdipong Sopajorn; Oktarina, Putu Santi (UHN IGB Sugriwa Denpasar, 2024)
The communication strategies used by students in the exchange program between UHN I Gusti Bagus Sugriwa Denpasar and Mahamakut Buddhist University were explored. A questionnaire based on Dörnyei’s Taxonomy was used to identify different strategies, including interactional, compensatory, achievement, and avoidance strategies. The findings show that students actively participated in communication despite challenges such as language skills and cultural differences. Interactional strategies, like asking for clarification and confirming understanding, were commonly used. Compensatory strategies, such as language switching and gestures, also helped convey messages more effectively. The results emphasize the importance of recognizing these strategies to support language learning and intercultural communication. Keywords: communication strategies, student exchange, Indonesian students, Thai students, intercultural communication, Dörnyei’s Taxonomy.